A feasibility study on the use of cranial nerve non-invasive neuromodulation to improve affected arm function in people in the chronic stage of a stroke - Maureen Ahiatsi; Guillaume Léonard; Eléonor Riesco; Marie-Claude Girard; Marie-Hélène Milot (BMC Neurology)
Abstract Background Chronic stroke survivors are often left with residual arm muscle weakness impeding arm function, daily life activities and quality of life. Exercise is one of the main post-stroke interventions to improve arm function, with cranial nerve non-invasive neuromodulation (CN-NINM) emerging as a potentially interesting complementary therapy to enhance its benefits. Only one study has evaluated the impact of CN-NINM combined with a lower-limb training program on improved balance in subacute stroke survivors. The aim of this study was to assess the feasibility and explore the effects on motor function of an arm strengthening program combined with CN-NINM in chronic stroke survivors (> 6 months). Methods Twelve (12) participants (69 ± 11 years) took part in this feasibility study. Recruitment and drop-out rates, number of people who elected not to participate, adherence and adverse events were collected to assess feasibility. The effects of CN-NINM + exercise on motor function were evaluated by changes in arm motor function, measured using the Fugl-Meyer Assessment (FMA), and functional performance, evaluated through the Wolf Motor Function Test (WMFT), following a 4-week arm strengthening program (60 min, 3 sessions/week) combined with CN-NINM (tongue stimulation, 20 min at a comfortable intensity). Descriptive and non-parametric statistics (Wilcoxon signed-ranks test) were used to describe feasibility data and explore CN-NINM effects. Results Feasibility was confirmed with a recruitment rate of 1.3 person/month, no dropout, a 100% adherence rate, and no serious adverse events. A significant gain in FMA (p = 0.003) with a trend for WMFT (P = 0.11) were noted post-intervention. Conclusion This study suggests that CN-NINM combined with an arm strengthening program is feasible and may improve arm function in chronic stroke survivors. Further research is needed to validate the results. Trial registration This clinical trial was registered on ClinicalTrials.gov (NCT05370274) on April 27, 2022.